Hybrid photonic assemblies based on 3D-printed coupling structures - Xu, Yilin (Karlsruhe Series in Photonics & Communications, 2023)
Photonic integrated circuits (PIC) become increasingly important for numerous applications. Mass production of PIC has become widely available, but large-volume low-cost photonic packaging still represents a challenge. Additive micro-fabrication of free-form optical coupling structures is discussed as a concept to overcome this technology gap. Multi-photon 3D-lithography is used to fabricate dielectric waveguides ("photonic wire bonds", PWB) as well as facet-attached microlenses (FaML).